Assessment of depression in total laryngectomy patients - Kelen Fernanda Catarochi; Vaneli Colombo Rossi; Carlos Takahiro Chone (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: Of this study was to evaluate the presence and severity of depressive symptoms in total laryngectomy patients and identify variations in results of each item on the depression scale. Methods: This study is a quantitative, analytical and cross-sectional study, with 30 total laryngectomized participants, using the Instrument (BDI-II) Beck Depression Inventory-II, from April to July 2024, all total laryngectomized participants who attended the Head and Neck surgery Otorhinolaryngology Outpatient Clinic and were invited to participate in the research, the assessment was carried out by the same reserarcher and the estimated response time was 22 min. Results: Show tha depression was identified in 20% of patients with mild symptoms, 13% moderate and 20% severe. The sleep pattern was altered in 63% of respondents and difficulty concentrating was reported by 57%. Altered appetit was identified in 53%. The feeling of sadness was identified in 60% of patients, also crying, pessimism and loss of interest in 40%. Regarding irritability, agitation and feelings of punishment, 47% of participants showed changes. The self-criticism and self-esteem were preserved in 70% and 63% respectively. Suicidal thoughts or desires were identified in 17% and any percentage for this resuts needs attention. The group was 80% male, the average age of participants is 65±7-years. Married patientes are 67%, divorced 20%, singles 3% and widower are 10%. The time after surgery ranged fron 1 to 10 years; 50% had undergone chemotherapy and 73% denied post-surgical complications. Conclusion: This this study points to is that 53% of patients showed signs of depression on some scale. Level of evidence: Level 3.